RNA N6-Methyladenosine Modifications and Its Roles in Alzheimer’s Disease - Zhang, Runjiao; Zhang, Yizhou; Guo, Fangzhen; Li, Sha; Cui, Huixian (Frontiers in Cellular Neuroscience, 2022)
The importance of epitranscriptomics in regulating gene expression has received widespread attention. Recently, RNA methylation modifications, particularly N6-methyladenosine (m6A), have received marked attention. m6A, the most common and abundant type of eukaryotic methylation modification in RNAs, is a dynamic reversible modification that regulates nuclear splicing, stability, translation, and subcellular localization of RNAs. These processes are involved in the occurrence and development of many diseases. An increasing number of studies have focused on the role of m6A modification in Alzheimer's disease, which is the most common neurodegenerative disease. This review focuses on the general features, mechanisms, and functions of m6A methylation modification and its role in Alzheimer’s disease.